ANALISIS MANAJEMEN SYARIAH FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENJUAL MEMASARKAN PRODUK SECARA ONLINE DI MASA PANDEMI COVID-19 (STUDI DI KECAMATAN PAMIJAHAN DAN KECAMATAN CIAMPEA, KABUPATEN BOGOR). - Irhamna, Wahyu; Trihantana, Rully; Suryani, Ermi (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
This study aims to determine the effect of product, location, and promotional factors on seller interest in marketing products online during the COVID-19 pandemic. The number of variables studied were four, consisting of three independent variables and one dependent variable. The population used in this study were all sellers in Pamijahan District and Ciampea District, Bogor Regency, with a sample of respondents using the Lemeshow method. The sampling method used probability sampling with simple random sampling technique. The data used are primary and secondary data using a questionnaire technique in the form of a Likert scale. The analytical method used is multiple linear regression analysis using IBM Statistical Package for Social Sciences (SPSS) Software Version 25. The results of this study indicate the influence of seller interest which consists of several factors, namely product, location and promotion together have a real and significant effect. positive. However, the location factor is more dominant which has a real and positive effect on seller interest, with a variable regression coefficient value of 6.283 which means that if the location increases by one unit, the seller's interest value will increase by 6.283